Organoleptic Characteristics of Mustard Flour (Brassica Juncea L) with Polyetilen and Polypropilen Packaging - Deni Windarti; Ida Agustini Saidi (Procedia of Engineering and Life Science, 2021)
This study aims to determine the changes in the characteristics of mustard flour by using organoleptics as a parameter of the assessment. Mustard flour is stored for 42 days with 2 types of plastic packaging, namely polypropylene and polyethylene. With 3 levels of storage temperature used are 20 oC, 30oC and 40oC. Organoleptic tests conducted among others color, aroma and sow power tests. Based on the tests that have been done, mustard flour undergoes changes in each temperature and type of packaging. Based on the research that has been done, mustard flour at all temperature levels and 2 types of packaging used during the storage process decreased.The best storage temperature on each package is 40oC and the best packaging for mustard flour is Polypropylene packaging.